Charity sport event participants and fundraising: An examination of constraints and negotiation strategies. Issue 3 (June 2020) - Filo, Kevin; Fechner, David; Inoue, Yuhei
Highlights: Fundraising is challenging for charity sport event (CSE) participants. CSE participants are confronted by donor's lack of interest and lack of funds. CSE participants are also confronted by a lack of time and discomfort in asking. Storytelling and giving prize incentives help overcome these fundraising challenges. Soliciting donations of any size can also assist in addressing these challenges. Abstract: Charity sport events provide participants with a meaningful event experience, and the opportunity to support a charitable cause is a critical component of this experience. This opportunity often involves fundraising, either as a requirement of event participation or as an option to supplement registration. However, fundraising as part of charity sport event participation is a difficult task. In the current research, the authors examine the challenges faced by charity sport event participants in soliciting donations, and the effort made to overcome these challenges. Constraint negotiation served as a theoretical framework to guide this examination. Semi-structured interviews ( N  = 27) were conducted with Triathlon Pink participants to discuss their fundraising process and their attitudes towards fundraising. Four constraints were revealed: lack of receptivity among potential donors, perceived lack of money from potential donors, discomfort in asking, and lack of time. These constraints were negotiated through three strategies: narrative, prizes and incentives, and emphasising that any bit helps. Based upon the themes uncovered, charity sport event managers can implement increased education of fundraisers and point of sale donations within the registration process.